E0096 The study on the relations between aldosterone and atrial interstitial remodelling and atrial fibrillation. (17th November 2010) - Luo, Taiyang; Liu, Xiaohui; Du, Xin; Liu, Xingpeng; Lei, Tao; Wang, Haiyun; Shi, Jiahai
Abstract : Objective: To investigate the relations between aldosterone (Ald) and atrial interstitial remodelling and atrial fibrillation (AF). Methods: 18 healthy male hybrid dogs aged 15–18 months were divided into three groups randomly, the control group (n=6), the Perindopril group (1 mg/kg/d, n=6), the Spironolactone group (10 mg/kg/d, n=6). To test the form and function of left atrial and plasma aldosterone levels before pacing and 4 weeks, 8 weeks after pacing, respectively. Observe the number of dogs maintained AF and duration of AF after cessation of pacing. Then, kill the animals and collect some tissues of left and right atrial to detect aldosterone levels and test the situation of atrial fibrosis by pathological examination. By comparing the similarities and differences between the three groups, to understand the impact of atrial interstitial remodelling and the occurrence and development of atrial fibrillation induced by aldosterone inhibitor. Results: The levels of plasma aldosterone were no significant differences between the three groups before pacing (p>0.05), while 4 weeks and 8 weeks after pacing the plasma aldosterone levels and the aldosterone levels of atrial tissue 8 weeks after pacing of the other groups were significantly lower than those of the control group (p<0.05). In the control group, 4 weeks and 8 weeks after pacing the plasma aldosterone levels was significantly higher than that before pacing (p<0.05), while in the other two groups, there were no significant differences between before and after pacing (p>0.05). Pacing for 4 weeks and 8 weeks later, the diameter, end-systolic volume and end-diastolic volume of the left atrium of the control group dogs significantly increased than before pacing, and left atrial ejection fraction (LAEF) lower than before pacing significantly (p<0.05). Compared with the control group, those of the Perindopril group and Spironolactone group after pacing significantly reduced, but LAEF significantly increased (p<0.05). Compared with the control group, the number of dogs maintained atrial fibrillation of the two treatment groups after cessation of pacing significantly reduced, with a shorter average duration of atrial fibrillation. While there was not significant difference between the two treatment groups. The value of Collagen Volume Fraction (CVF) of the Control group was significantly higher than those of the other two groups (p<0.05), while no significant difference value between the two treatment groups (p>0.05). Conclusion: The aldosterone receptor antagonist (spironolactone) and ACEI (Perindopril) can inhibit aldosterone levels and atrial fibrosis, improve the changes of atrial structure and function, and reduce the incidence and duration of atrial fibrillation. And the effects of the two drugs are similar.